2016
DOI: 10.5603/fm.a2015.0130
|View full text |Cite
|
Sign up to set email alerts
|

The sciatic nerve in human cadavers — high division or low formation?

Abstract: Variations of the sciatic nerve have been extensively studied in the past (Folia Morphol 2016; 75, 3: 306-310)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Studies on 24 Malaysian and 102 American cadavers have reported 83.4% and 88.2% type-a relations and 16.6% and 11.8% type b-f relations, respectively; however, type-d, type-e, and type-f relations were absent, which was also noticed in current study [24,25]. A research on 120 American cadavers detected 97.5% type-a and 2.5% type-b relations, which was almost similar to our study [12].…”
Section: Discussionsupporting
confidence: 75%
“…Studies on 24 Malaysian and 102 American cadavers have reported 83.4% and 88.2% type-a relations and 16.6% and 11.8% type b-f relations, respectively; however, type-d, type-e, and type-f relations were absent, which was also noticed in current study [24,25]. A research on 120 American cadavers detected 97.5% type-a and 2.5% type-b relations, which was almost similar to our study [12].…”
Section: Discussionsupporting
confidence: 75%
“…of SN, the TN and CFN, develop separately during early embryogenesis as fusions of the dorsal and ventral divisions of the ventral rami of the lower lumbar and sacral spinal nerves [1,2,5,9]. These components maintain their individual identities throughout their development, though they share an epineural sheath to form SN immediately distal to the lumbosacral plexus [1,2,10]. Stochastic and precipitate division of SN into its major components along its course could give rise to the variations observed in SN structure relative to the PM.…”
Section: Fig 2 Classification Of Relationship Of the Piriformis And S...mentioning
confidence: 99%
“…The sciatic nerve may have an iatrogenic injury, with the most frequent mechanisms of intraoperative nerve damage, including stretching and direct injury due to compression or laceration [2,8]. The sciatic nerve can be subjected to traction forces during procedures such as total hip arthroplasty, especially when this procedure is performed via a posterior approach [9]. The sciatic nerve can also be damaged after a traumatic posterior hip dislocation, especially in cases where there is a coexistence of variations in this which likely increases the risk of injury [10].…”
Section: Introductionmentioning
confidence: 99%